2016
DOI: 10.1111/ejn.13187
|View full text |Cite
|
Sign up to set email alerts
|

Striatonigral control of movement velocity in mice

Abstract: The basal ganglia have long been implicated in action initiation. Using three-dimensional motion capture, we quantified the effects of optogenetic stimulation of the striatonigral (direct) pathway on movement kinematics. We generated transgenic mice with channelrhodopsin-2 expression in striatal neurons that express the D1-like dopamine receptor. With optic fibres placed in the sensorimotor striatum, an area known to contain movement velocity-related single units, photo-stimulation reliably produced movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…Recent work has shown that sensorimotor SPN activity is often highly correlated with movement velocity (Kim et al, 2014;Yttri and Dudman, 2016), and stimulation of striatal output frequency-dependently determines movement velocity (Bartholomew et al, 2016). Yet it remains unclear how, during target-driven pursuit behavior, the striatal output is commanded by representation of distance to target.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that sensorimotor SPN activity is often highly correlated with movement velocity (Kim et al, 2014;Yttri and Dudman, 2016), and stimulation of striatal output frequency-dependently determines movement velocity (Bartholomew et al, 2016). Yet it remains unclear how, during target-driven pursuit behavior, the striatal output is commanded by representation of distance to target.…”
Section: Introductionmentioning
confidence: 99%
“…The neural activity that occurs in between experimenter-defined events is usually neglected. However, recent work has shown that continuous behavioral measurements with high spatial and temporal resolution can reveal previously neglected relationships between neural activity and behavior (Barter et al, 2014(Barter et al, , 2015aKim et al, 2014Kim et al, , 2019Bartholomew et al, 2016;Hughes et al, 2019). Our system demonstrates that, with continuous behavior measures, neural activity outside of these observed defined timepoints becomes intelligible.…”
Section: Discussionmentioning
confidence: 79%
“…Although there is significant literature supporting a role for these inputs in action selection or initiation, there are certainly other possibilities. One such idea is that Str inputs encode movement velocity and the resulting SNr firing rate encodes spatial position ( Kim et al, 2014 ; Bartholomew et al, 2016 ; Barter et al, 2015 ). If we apply our modeling results to this view, then we predict that the Cl − load from the GPe, by tuning SNr responses to GABAergic inputs from Str, could impact velocity with which selected movements are performed.…”
Section: Discussionmentioning
confidence: 99%